Satyricon - Petronius Arbiter -66; Seneca, Lucius Annaeus Philosophus -65 (Harvard University Press, 2020)
"The Latin Satyrica is often referred to as a satire of early imperial manners, especially of freedmen, slaves, and marginal characters from the Greek-speaking Near East. Most of the names of the characters are Greek, and the action of the extant Satyrica takes place in predominantly Greek southern Italy, first in the area around the Bay of Naples and later in Croton. If the Satyrica is satire, it is of a most gentle and general kind. The characters created by Petronius are both ill-mannered and sympathetic, and they are creations in fiction. The reader of the Satyrica recognizes from the first words that the work is extant only in fragments, and that much that had been narrated by Encolpius has been lost. In addition, attached to the Latin text of the Satyrica is a collection of fifty-one fragments from disparate sources, which with varying degrees of certitude have been attributed to the Arbiter, Petronius, or the Satyrica (but no one knows where, or even if, these fragments actually belong in the work). The short satirical pamphlet of about fifteen pages of Latin on the death, apotheosis, and attempt to enter heaven by the Roman emperor Claudius (10 BC-AD 54; r. 41-54) is almost certainly entitled Apocolocyntosis (hereafter, Apoc.), and very likely the work of the amateur philosopher and super-rich landowner Lucius Annaeus Seneca, also known as Seneca the Younger, or just Seneca (4 BC-AD 65)"--